Epidemiological study of orthopedic injuries in hemodialysis patients in Taiwan: a fixed cohort survey, 2004–2008 - Chang, Nien-Tzu (Dove Medical Press, 2013)
BACKGROUND: The burden of chronic kidney disease (CKD) is a growing concern worldwide. The prevalence of hemodialysis in Taiwan is the highest in the world, and this may increase the prevalence of orthopedic fractures. The aim of this study was to explore the incidences of various orthopedic injuries and the related risk factors. METHODS: A nationwide prospective study based on the Taiwan National Health Insurance dataset was conducted during 2004–2008. A total of 82,491 CKD patients were selected as the fixed cohort population. The International Classification of Diseases 9-CM diagnosis codes and treatment codes were identified as the inclusion criteria for orthopedic injury. RESULTS: A total of 82,491 Taiwanese people with CKD were identified in 2004, and 4915 orthopedic injuries occurred during the 5-year follow-up period. The cumulative incidences of orthopedic injuries were 42.56‰ for lower limb fractures, and 12.93‰, 3.27‰, and 1.64‰ for upper limb fractures, vertebrae fractures, and joint dislocations, respectively. All three types of orthopedic fractures were more common in the oldest age stratum (≥65 years old). In the CKD patients, the risk ratio of osteoporosis was 3.47 (95% confidence interval, 3.10–3.89) for all orthopedic injuries. Patients of advanced age, the female gender, and those with high comorbidity were also at significant risk of sustaining orthopedic fractures. CONCLUSION: The results from this Taiwanese CKD cohort support the strong influence of aging and osteoporosis on all kinds of orthopedic injuries. The postponing of osteoporosis may need to be taken into consideration for the prevention of orthopedic injury among CKD patients undergoing hemodialysis.